A simplified method to estimate the run-off in Periglacial Creeks: a case study of King George Islands, Antarctic Peninsula. (14th May 2018) - Falk, Ulrike; Silva-Busso, Adrián; Pölcher, Pablo
Abstract : Although the relationship between surface air temperature and glacial discharge has been studied in the Northern Hemisphere for at least a century, similar studies for Antarctica remain scarce and only for the past four decades. This data scarcity is due to the extreme meteorological conditions and terrain inaccessibility. As a result, the contribution of glacial discharge in Antarctica to global sea-level rise is still attached with great uncertainties, especially from partly glaciated hydrological basins as can be found in the Antarctic Peninsula. In this paper, we propose a simplified model based on the Monte Carlo method and Fourier analysis for estimating discharge in partly glaciated and periglacial hydrological catchments with a summer melt period. Our model offers the advantage of scarce data requirements and quick recognition of periglacial environments. Discharge was found to be highly correlated with surface air temperature for the partially glaciated hydrological catchments on Potter Peninsula, King George Island (Isla 25 Mayo). The model is simple to implement and requires few variables to make most versatile simulations. We have obtained a monthly simulated maximum flow estimates between 0.74 and 1.07 m 3 s −1 for two creeks (South and North Potter) with a very good fit to field observations. The glacial mean monthly discharge during summer months was estimated to 0.44±0.02 m 3 s −1 for South Potter Creek and 0.55±0.02 m 3 s −1 for North Potter Creek. This article is part of the theme issue 'The marine system of the West Antarctic Peninsula: status and strategy for progress in a region of rapid change'.